Deciphering the Neuronal Circuitry Controlling Local Blood Flow in the Cerebral Cortex with Optogenetics in PV::Cre Transgenic Mice - Urban, Alan; Rancillac, Armelle; Martinez, Lucie; Rossier, Jean (Frontiers in Pharmacology, 2012)
Although it is know since more than a century that neuronal activity is coupled to blood supply regulation, the underlying pathways remains to be identified. In the brain, neuronal activation triggers a local increase of cerebral blood flow (CBF) that is controlled by the neurogliovascular unit composed of terminals of neurons, astrocytes and blood vessel muscles. It is generally accepted that the regulation of the neurogliovascular unit is adjusted to local metabolic demand by local circuits. Today experimental data led us to realize that the regulatory mechanisms are more complex and that a neuronal system within the brain is devoted to the control of local brain blood flow. Recent optogenetic experiments combined with functional magnetic resonance imaging (fMRI) have revealed that light stimulation of neurons expressing the calcium binding protein parvalbumin (PV) is associated with positive blood oxygen level-dependent (BOLD) signal in the corresponding barrel field but also with negative BOLD in the surrounding deeper area. Here, we demonstrate that in acute brain slices, ChR2-based photostimulation of PV containing neurons gives rise to an effective contraction of penetrating arterioles. These results support the neurogenic hypothesis of a complex distributed nervous system controlling the CBF.